Effect of stress management intervention I and II: relaxation and combination techniques (relaxation and lemon turmeric and honey) on the stress level of comorbid respondents during the COVID-19 pandemic in west Bogor district - Surtiati, Eti; Ngadiarti, Iskari; Sunita, Anna; Ariani, Ni Putu; Palestina, Bondan; Nuraini, Ati; Salmid, Amid; Riyanto (International Journal Of Community Medicine And Public Health, 2024)
Background: This study aimed to determine the effect of stress management I: progressive relaxation & 5 fingers, and stress management II: relaxation (progressive and 5 fingers) with lemon turmeric honey (lemonyit honey) on the stress level of cormobid respondents in the COVID-19 pandemic era. Methods: The research design was a quasi-experimental pre-test and post-test control group. The location was in the area with the highest Covid-19 cases and Rukun Warga (RW) with the largest population, namely West Bogor Subdistrict in Curug and Cilendek RW. The study population was all residents aged adults to pre elderly. Samples were taken randomly, by first screening for hypertension, diabetes and respiratory disorders in adults-pre elderly. Samples that fit the inclusion and exclusion criteria were obtained 100 respondents, consisting of 3 groups; namely group 1 = 34 people received progressive relaxation techniques and five fingers for 60-90 minutes, group 2 = 30 people received a combination of relaxation techniques and lemonyit honey, and group 3 (control) = 36 people. Stress levels were measured using the Kurzen stress questionnaire. Data analysis included descriptive analysis and hypothesis testing. Results: Stress management I and II, effectively controlling stress levels in the Covid-19 pandemic era in comorbid respondents. Conclusions: Stress management I and II can reduce stress levels during the Covid-19 pandemic in respondents with cormobid. Stress management I and II, can be applied in health care facilities both in hospitals and communities during the Covid-19 pandemic, to reduce the stress levels of clients who have cormobid.